Wolbachia transcription elongation factor "Wol GreA" interacts with α2ββ'σ subunits of RNA polymerase through its dimeric C-terminal domain. - Jeetendra Kumar Nag; Nidhi Shrivastava; Dhanvantri Chahar; Chhedi Lal Gupta; Preeti Bajpai; Shailja Misra-Bhattacharya (Public Library of Science (PLoS), 2014)
OBJECTIVES: Wolbachia, an endosymbiont of filarial nematode, is considered a promising target for therapy against lymphatic filariasis. Transcription elongation factor GreA is an essential factor that mediates transcriptional transition from abortive initiation to productive elongation by stimulating the escape of RNA polymerase (RNAP) from native prokaryotic promoters. Upon screening of 6257 essential bacterial genes, 57 were suggested as potential future drug targets, and GreA is among these. The current study emphasized the characterization of Wol GreA with its domains. METHODOLOGY/PRINCIPAL FINDINGS: Biophysical characterization of Wol GreA with its N-terminal domain (NTD) and C-terminal domain (CTD) was performed with fluorimetry, size exclusion chromatography, and chemical cross-linking. Filter trap and far western blotting were used to determine the domain responsible for the interaction with α2ββ'σ subunits of RNAP. Protein-protein docking studies were done to explore residual interaction of RNAP with Wol GreA. The factor and its domains were found to be biochemically active. Size exclusion and chemical cross-linking studies revealed that Wol GreA and CTD exist in a dimeric conformation while NTD subsists in monomeric conformation. Asp120, Val121, Ser122, Lys123, and Ser134 are the residues of CTD through which monomers of Wol GreA interact and shape into a dimeric conformation. Filter trap, far western blotting, and protein-protein docking studies revealed that dimeric CTD of Wol GreA through Lys82, Ser98, Asp104, Ser105, Glu106, Tyr109, Glu116, Asp120, Val121, Ser122, Ser127, Ser129, Lys140, Glu143, Val147, Ser151, Glu153, and Phe163 residues exclusively participates in binding with α2ββ'σ subunits of polymerase. CONCLUSIONS/SIGNIFICANCE: To the best of our knowledge, this research is the first documentation of the residual mode of action in wolbachial mutualist. Therefore, findings may be crucial to understanding the transcription mechanism of this α-proteobacteria and in deciphering the role of Wol GreA in filarial development.